2017
DOI: 10.5942/jawwa.2017.109.0121
|View full text |Cite
|
Sign up to set email alerts
|

Scale Formation Under Blended Phosphate Treatment for a Utility With Lead Pipes

Abstract: US corrosion control practice often assumes that the orthophosphate component of blended phosphate corrosion inhibitors causes the formation of low‐solubility lead–orthophosphate solids that control lead release into drinking water. This study identified the solids that formed on the interior surface of a lead service line and a galvanized steel pipe excavated from a system using a proprietary blended phosphate chemical. The scale was analyzed by X‐ray diffraction, X‐ray fluorescence, and scanning electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 37 publications
4
79
0
Order By: Relevance
“…Theoretically, higher concentrations of orthophosphate, with no interfering polyphosphate complexation, could potentially improve lead release by the formation of a less‐soluble Pb(II) orthophosphate scale. This notion of amorphous phases functioning as protection mechanisms has been previously discussed by Wasserstrom et al ().…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…Theoretically, higher concentrations of orthophosphate, with no interfering polyphosphate complexation, could potentially improve lead release by the formation of a less‐soluble Pb(II) orthophosphate scale. This notion of amorphous phases functioning as protection mechanisms has been previously discussed by Wasserstrom et al ().…”
Section: Resultsmentioning
confidence: 69%
“…Crystalline phases in the outer layers of a pipe scale act more as passivating films formed by the direct pipe–water interaction, whereas amorphous phases were more analogous to accumulating deposits on the pipe scale surface. Wasserstrom et al () observed the dominance of mixed‐metal amorphous phases within lead pipe scales from a blended‐phosphate system in the Great Lakes Region (United States). In this study, a little over one‐third of the systems (four GW and five SW systems) had an amorphous phase detectable by XRD, coexisting with crystalline phases (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations